PENGENDALIAN Conopomorpha cramerella Snell MENGGUNAKAN FEROMON SEKS DI DESA MAKARTI JAYA KABUPATEN POHUWATO PROVINSI GORONTALO - Muliku, Stevenlly J.; Tulung, M.; Pinaria, B. A.N. (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ Cocoa is one of the agricultural products that have a big role, especially in terms of employment, regional development, increasing farmer welfare and increasing revenues/foreign exchange. One of the main pests is the cruncher of cocoa C. cramerella Snell. The research aims to get the technology of environmentally friendly cacao borer pest control through the use of sex pheromone traps. The study was conducted in Makarti Jaya Village, Pohuwato District, Gorontalo Province for 3 months (January - March 2017), using Randomized Block Design (RAK), with 3 treatments and 6 replications. The result of the research is the use of the six traps of pheromone sex succeeded in decreasing the intensity of PBK pest attack, after one month of attack intensity attack trapping decreased to 2.23%, lower than pesticide application which only 4.49%.Keywords: pheromone sex Conopomorpha cramerella Snell, cacao fruit snipper